2019
DOI: 10.1177/0003489419867976
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Septal Splints: Prophylactic Antibiotics and Nasal Microbiology

Abstract: Objectives: Intranasal septal splints are often used in nasal septal surgeries. Routine use of postoperative antibiotics is an accepted practice, although data regarding its efficacy in preventing postsurgical complications are limited. This study aimed to examine bacterial colonization on septal splints following prophylactic antibiotic therapy and the association with postoperative infections. Methods: Fifty-five patients underwent septoplasty by a single surgeon between March 2015 and April 2016. All had in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…Several investigators paid attention to bacterial profiles in relation to IP/intranasal splints (IP/IS) [5] , [6] , [7] , while we looked at SARS-CoV-2 shedding post-symptom in INBF patients. 40-87% of IP/IS are found to be contaminated, for example, with Staphylococcus aureus , and Enterobacteriaceae sp., and linked to serious complications, such as toxic shock syndrome, endocarditis, meningitis, and cavernous sinus thrombosis [5] , [6] , [7] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several investigators paid attention to bacterial profiles in relation to IP/intranasal splints (IP/IS) [5] , [6] , [7] , while we looked at SARS-CoV-2 shedding post-symptom in INBF patients. 40-87% of IP/IS are found to be contaminated, for example, with Staphylococcus aureus , and Enterobacteriaceae sp., and linked to serious complications, such as toxic shock syndrome, endocarditis, meningitis, and cavernous sinus thrombosis [5] , [6] , [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators paid attention to bacterial profiles in relation to IP/intranasal splints (IP/IS) [5] , [6] , [7] , while we looked at SARS-CoV-2 shedding post-symptom in INBF patients. 40-87% of IP/IS are found to be contaminated, for example, with Staphylococcus aureus , and Enterobacteriaceae sp., and linked to serious complications, such as toxic shock syndrome, endocarditis, meningitis, and cavernous sinus thrombosis [5] , [6] , [7] . We prescribed a course of antibiotics for our patients because of delayed treatment with re-fracturing, subsequent mucosal breakdown, and nasal packing for 24-72 hours, in agreement with other authors [5] , [6] , [7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the analysed study populations in the review by Georgiou et al were rather small, varying from groups of 35 to 174 patients. This is often the case in studies examining the effects of prophylactic antibiotics in septoplasty [14][15][16]18], which automatically makes it difficult to reach proper statistical significance to prove their effect. Two of the studies analysed by Georgiou et al had considerably larger study populations (1040 and 2000 rhinoplasty patients) and both reported only few postoperative infections (0.48% and 0.6%, respectively), whereas our study presented noticeably higher rates, as high as 5.3%.…”
Section: Discussionmentioning
confidence: 99%